NARASI TENTANG MITOS KECANTIKAN DAN TUBUH PEREMPUAN DALAM SASTRA INDONESIA MUTAKHIR: STUDI ATAS KARYA-KARYA CERPENIS INDONESIA - Suarni Syam Saguni; Baharman Baharman (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2016)
Abstract: Every day women are convinced by the myths of beauty that plunge into the cult of beauty. Therefore, this study aims "to describe the forms of narratives on the myth of beauty and the female body and female figures acceptance and resistance against the myth of beauty and the female body. The study design was a qualitative descriptive analysis using a knife Roland Barthes mythology theory and feminism. The data in this study is qualitative data and the data source is the latest Indonesian short stories. Results showed that some of the beauty myth that socialized among sempuna pretty mean physically, symmetrical, sexy, lovable, white, slim body, stylish appearance, flexible and practical. Beauty is based on the research results can become the new oppressors of women. The public has great power over the meaning of women against him. In relation pe-maknaan's, women's position as the object of the oppressed because the meaning itself is largely determined by social significance. The social construction of the meaning of these women will be internalized in the consciousness of women and serve as a standard within the meaning reproducing itself.